TFP shocks and endogenous innovation ability in manufacturing industry: from the perspective of structural stickiness - Zhao, Dangru; Zhao, Tianshu; Du, Ran (Technological and Economic Development of Economy, 2025)
This paper identifies the systemic shocks of total factor productivity (TFP) at the macro level and industry level, and then evaluates the structural stickiness of TFP shocks by using information entropy and industry correlation degree through counterfactual structural simulation based on China’s manufacturing companies. We find that: in the face of TFP systemic shocks, the industries with less structural stickiness include computer communication and other electronic equipment manufacturing, special equipment manufacturing and general equipment manufacturing, indicating that these industries have a strong internal innovation power. The TFP distribution of electrical machinery and equipment manufacturing industry and ferrous metal smelting and rolling industry showed structural differentiation, and the lower tail enterprises are not sensitive to TFP shocks. The industries with strong structural stickiness are non-ferrous metal processing industry and non-metallic mineral products industry, etc., which have weak internal innovation power and need exogenous innovation incentives. In addition, there is a significant positive correlation between industry correlation and information entropy, which emphasizes the radiation effect role of industries with high industry correlation degree. The research provides a new method to evaluate the innovation ability of the industry and a basis for the differentiation of innovation incentive policies in the industry. First published online 15 November 2024